SELF-CONCORDANCE AND SELF-EFFICACY IN PERSONAL GOALS: WHAT IS THEIR CONTRIBUTION TO WELL-BEING? - Sansinenea, Eneko; Gil de Montes, Lorena; Agirrezabal, Arrate; Larrañaga, Maider; Ortiz, Garbiñe; Valencia, José Francisco; Fuster, María José (Anales de Psicología / Annals of Psychology, 2008)
In this study the relationship between self-efficacy and self-concordance of personal goals and well-being was investigated. The goal was to examine the structure of self-concordance (Sheldon, 1999), as well as to check the predictive value of self-efficacy and self-concordance on well-being. University students (N=329) rated the self-concordance and self-efficacy perceptions upon their three most valued personal goals. Indeed, measures of positive and negative affect and physical symptoms reports were also obtained. Results show that the self-concordance structure fits the model, and that both self-efficacy and self-concordance were necessary to predict positive affect, whereas self-efficacy was sufficient to predict negative affect and physical symptoms. Implications for this differentiation in relationships with affect and well-being are discussed.